Phenolic compounds from Syzygium jambos (Myrtaceae) exhibit distinct antioxidant and hepatoprotective activities in vivo - Sobeh, Mansour; Esmat, Ahmed; Petruk, Ganna; Abdelfattah, Mohamed A. O.; Dmirieh, Malak; Monti, Daria Maria; Abdel-Naim, Ashraf B.; Wink, Michael (Journal of functional foods, 2018)
HPLC-PDA-MS/MS analysis of Syzygium jambos leaf extract allowed the identification of 17 secondary metabolites, including flavonol glycosides, flavonol di-glycosides, and flavones as well as ellagitannins and phenolic acids. The extract showed promising antioxidant activities in different experimental models. In Caenorhabditis elegans, the extract mediated a dose dependent survival rate and decreased the intracellular ROS level and HSP-16.2 expression. In a rat model against acute CCl4 intoxication, the extract reduced the levels of all tested liver markers ALT, AST, TB, TC, TG, and MDA and increased GSH and SOD; effects were similar to those of silymarin. In hepatocytes, pre-treatment with the extract inhibited ROS production, against the deleterious effects of sodium arsenite, and increased GSH levels, without alteration in the phosphorylation levels of p38 and of its direct target, MAPKAPK-2. These results demonstrate the high efficacy of S. jambos extract in free radical-scavenging, and inhibition of reactive oxygen species.
Gesehen am 16.02.2018